Development and validation of the Chinese coaches’ interpersonal style scale - Su, Wen; Zhao, Daliang (Frontiers in Psychology, 2023)
Purpose: Coaches' behaviors and coaching styles play a critical role in influencing athletes' psychological experiences and performance. According to the self-determination theory (SDT), coaches' interpersonal behaviors are commonly categorized as autonomy-supportive and controlling. Due to less focus on the unique behaviors of Chinese coaches, this study incorporated coaches' parental care for athletes, referred to as paternalistic benevolence, in their interpersonal styles in the context of the Chinese culture.Methods: Exploratory factor analyses were used in studies 1 and 2 to find items associated with benevolent coaching behaviors and items to create the Chinese Coaches' Interpersonal Style Scale. Study 3 used the constructed scale, as well as the Subjective Vitality Scale and Athlete Burnout Questionnaire, with a sample of athletes to examine scale reliability. The 15-item Chinese Coaches' Interpersonal Style Scale contained three dimensions: benevolent, autonomy-supportive, and controlling coaching styles.The findings showed that: (1) benevolent coaching behaviors held significant explanatory weight in the Chinese cultural context; (2) controlling and autonomy-supportive coaching styles were culturally congruent among both Eastern and Western athletes; and (3) benevolent and autonomysupportive coaching behaviors positively impacted athletes, whereas controlling coaching behaviors had a negative impact.The measure showed strong validity and reliability, making it useful for future practice and research on the interpersonal style of Chinese coaches.